Conductive paint for lithium battery and production process thereof
By modifying acrylic emulsion to form a micro-crosslinked network and chemically anchoring conductive agent particles, the problem of easy damage to the conductive network in lithium battery conductive coatings during long-term cycling is solved, achieving a highly stable and chemically stable conductive coating.
Patent Information
- Application Number
- CN202611087101.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-11-03
AI Technical Summary
Existing conductive coatings for lithium batteries are prone to damage to their conductive networks during long-term charge-discharge cycles, leading to increased contact resistance. Furthermore, water-based systems suffer from insufficient adhesion strength and flexibility.
Modified acrylic emulsion is used as a binder. By forming a micro-crosslinked network and chemically anchored conductive agent particles in the coating, a stable hybrid three-dimensional conductive mesh is constructed. Combined with fluorinated acrylate monomers, the chemical stability and adhesion strength of the coating are improved.
It significantly improves the electron transport stability and electrolyte corrosion resistance of the coating, ensuring the durability and reliability of the electron transport path under long-term cycling and thermal stress.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fluorocarbon coating technology, specifically, it relates to a conductive coating for lithium batteries and its production process. Background Technology
[0002] As the mainstream electrochemical energy storage device, the further improvement of lithium batteries relies on the continuous optimization of the interface engineering of various components. Among them, the conductive coating of the current collector (also known as the "pre-coating" or "undercoating") is one of the key technologies for improving the battery interface performance. This coating is applied between the positive electrode current collector (usually aluminum foil) and the positive electrode active material layer. Its main functions are to reduce the contact resistance between the current collector and the active material, enhance the adhesion between the two, and suppress interfacial side reactions, thereby improving the battery's rate performance, cycle life, and energy density.
[0003] Conductive coatings typically consist of conductive agents (such as carbon black, carbon nanotubes, and graphene), binders, solvents, and other additives. Based on the binder system, they can be mainly divided into oil-based and water-based systems. Oil-based systems are represented by polyvinylidene fluoride (PVDF), which, thanks to the strong stability of the CF bond, exhibits excellent chemical and electrochemical inertness, resistance to electrolyte corrosion, and a certain degree of bonding strength. However, the processing of PVDF heavily relies on toxic and harmful organic solvents such as N-methylpyrrolidone (NMP), increasing production costs and environmental pressure, as well as posing health and safety risks. Water-based systems, represented by various water-based acrylic resins, use water as the dispersion medium and have significant advantages such as being environmentally friendly, low-cost, and safe in the process, making them an important development direction for the industry.
[0004] However, existing conductive coating technologies all face a fundamental structure-performance contradiction: the electronic conduction of the coating depends entirely on the physical contact between conductive agent particles. To form an effective three-dimensional conductive network in the binder matrix, the amount of conductive agent added must exceed its theoretical percolation threshold. Excessive conductive agent content severely dilutes the binder phase, leading to a decrease in the overall bonding strength and flexibility of the coating. More critically, during long-term charge-discharge cycles, the electrode active materials undergo repeated volume expansion and contraction, generating continuous mechanical stress. Simultaneously, the swelling effect of the electrolyte and changes in operating temperature induce relaxation, creep, and even localized dissolution of the polymer binder molecular chains. These factors collectively cause irreversible plastic deformation of the binder matrix, resulting in the displacement and separation of the conductive agent particle network, which was originally maintained by physical contact. This disrupts the conductive pathways and significantly increases the interfacial contact resistance. This problem is particularly prominent in applications emphasizing rapid charge-discharge and ultra-long cycle life. For waterborne acrylate systems, the polymer segments usually contain more hydrophilic groups, and the swelling phenomenon in the electrolyte environment is often more obvious than that of PVDF. Therefore, the problem of conductive network degradation caused by polymer matrix relaxation is also more severe.
[0005] Therefore, solving the problem of dynamic stability of conductive networks in conductive coatings, and developing conductive coatings for lithium batteries that are environmentally friendly, have excellent adhesion and electrochemical stability, is of great significance for promoting the development of high-performance lithium batteries. Summary of the Invention
[0006] In order to solve the technical problems mentioned in the background art, the purpose of this invention is to provide a conductive coating for lithium batteries and its production process.
[0007] The objective of this invention can be achieved through the following technical solutions: A conductive coating for lithium batteries comprises: 10-15 wt% conductive agent, 0.2-0.3 wt% wetting agent, 0.1-0.15 wt% defoamer, and 0.3-0.4 wt% thickener, with the balance being modified acrylic emulsion and deionized water, and a solid content of 17-23%.
[0008] The modified acrylic emulsion is prepared by the following method: Step A1: Under dry nitrogen protection, 3-aminopropyltriethoxysilane, chloromonool and anhydrous tetrahydrofuran are stirred and mixed evenly. The temperature is controlled in a water bath at 40-55℃. Triethylamine is slowly added and stirred for 5-8 hours. After the reaction is completed, the mixture is cooled to room temperature, the precipitated triethylamine salt is removed by filtration, and tetrahydrofuran is recovered by rotary evaporation to obtain the intermediate. Preferably, the chloromonool is one of 4-chlorobutanol and 8-chlorooctanol; it has good reactivity and economy, and the appropriate alkyl chain substitution can control the steric hindrance of subsequent reactions of the intermediate. Furthermore, the molar ratio of 3-aminopropyltriethoxysilane to chloromonool is 1:2.1-2.2; the chloromonool undergoes an amino substitution reaction with 3-aminopropyltriethoxysilane.
[0009] Step A2: Under dry nitrogen protection, the intermediate and anhydrous dichloromethane are stirred and mixed evenly. After cooling in an ice-water bath, methacryloyl chloride is slowly added and stirred for 1-1.5 hours. Then, the reaction is continued at room temperature for 2-3 hours. After the reaction is completed, dichloromethane is recovered by rotary evaporation to obtain the modified monomer. Furthermore, the molar ratio of the intermediate to methacryloyl chloride is 1:2; the methacryloyl chloride undergoes an esterification reaction with the substituted hydroxyl groups on the intermediate molecule.
[0010] Step A3: Mix the hydrophilic acrylic monomer, modified monomer, fluorinated acrylate monomer and emulsifier, then add deionized water for shear emulsification, purge with nitrogen for protection, heat to 75-90℃, slowly add ammonium persulfate solution and stir for 3-4 hours, cool and adjust the pH to 8 with ammonia water to obtain modified acrylic emulsion. Furthermore, the molar ratio of hydrophilic acrylic monomer, modified monomer and fluorinated acrylate monomer is 1:0.17-0.22:0.1-0.13; after copolymerization, a block polymer emulsion is formed.
[0011] Preferably, the conductive agent is a mixture of conductive carbon black and carbon nanotubes in a weight ratio of 1:0.12-0.18. The particulate carbon black and the rod-shaped carbon nanotubes form a three-dimensional spatial structure, which increases the contact probability of the conductive agent and improves its conductivity.
[0012] A production process for a conductive coating for lithium batteries includes: premixing a wetting agent, a defoamer, and deionized water; adding a conductive agent for shear dispersion; then adding a modified acrylic emulsion for mixing and defoaming; and finally adding a thickener for thorough mixing to obtain the conductive coating.
[0013] The beneficial effects of this invention are: The core technology of the conductive coating for lithium batteries and its preparation method provided by this invention lies in providing a modified acrylic resin-based binder with unique bifunctional groups. This binder fundamentally reconstructs the microstructure of the coating through a dual reaction mechanism within its molecular structure, as detailed below: First, the dimethacrylate groups derived from the modified monomers in the modified acrylic resin can undergo free radical copolymerization and crosslinking with other acrylate segments, forming a moderately crosslinked three-dimensional polymer network within the coating. This "micro-crosslinking" structure significantly enhances the bulk strength, elastic modulus, and creep resistance of the polymer matrix, providing the coating with excellent dimensional stability and a basic framework to resist electrolyte swelling. Compared to the chain segment relaxation and plastic flow that are prone to occur in linear polymers, this crosslinked network can more effectively lock in the overall structure and resist the continuous mechanical stress generated during battery cycling.
[0014] Specifically, the triethoxysilane groups located at the nodes of this cross-linked network undergo hydrolysis in an aqueous environment to generate highly reactive silanol groups. These silanol groups can undergo two crucial types of coupling reactions: first, a condensation reaction with oxygen-containing functional groups on the surface of the conductive agent to form strong covalent bonds; second, a similar reaction with hydroxyl groups on the surface of the aluminum foil current collector. These two types of reactions chemically anchor the originally physically dispersed conductive agent particles to the micro-cross-linked polymer network nodes, while simultaneously achieving a strong chemical bond between the coating and the current collector substrate; thus constructing a stable "organic (polymer network) - inorganic (conductive agent / current collector)" hybrid three-dimensional reinforced structure with chemical bonds as the connection points.
[0015] More importantly, these anchored conductive particles are no longer randomly dispersed, easily slippery "fillers," but rather "electron transport hubs" chemically fixed to network nodes with defined positions. These hubs are interconnected by flexible yet robust polymer segments, forming a conductive grid that is both rigid and flexible, with a stable topological structure. Even under long-term electrochemical cycling and thermal stress, when the polymer matrix undergoes minor deformation, these "hubs," as the core of electron transport, can maintain their relative positional stability, ensuring the durability and reliability of the electron transport path. This is analogous to the towers in a macroscopic power grid, stably receiving current transmitted between adjacent towers, thereby constructing a stable electron transmission path.
[0016] Furthermore, by introducing fluorinated acrylate monomers into the copolymerization process, the modified acrylic resin prepared in this invention belongs to the category of waterborne fluorocarbon resins. The introduction of fluorine structures forms an inert "armor" locally in the polymer chain segments, endowing the coating with certain resistance to chemical corrosion and oxidation by electrolytes, and inhibiting the swelling and penetration of electrolyte molecules into the polymer network. Moreover, the fluorinated segments and hydrophilic acrylic segments form an "amphiphilic" structure in the polymer molecules. This structure can spontaneously migrate to the surface of latex particles during emulsion preparation. The fluorinated segments point inward to enhance stability, while the hydrophilic segments point towards the aqueous phase to ensure dispersibility. This significantly improves the stability, mechanical shear stability, and film density of the resin emulsion itself, laying a solid technological foundation for the preparation of high-performance coatings. Detailed Implementation
[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0018] Example 1: Preparation of conductive coating for lithium batteries. The specific implementation process is as follows: I. Preparation of Modified Acrylic Emulsion Step A1: Dry nitrogen gas is introduced into the reaction system, and 3-aminopropyltriethoxysilane, 4-chlorobutanol and anhydrous tetrahydrofuran are added and stirred until homogeneous. The mixture is heated to 40°C in a water bath, and triethylamine is slowly added and stirred for 8 hours. The raw material amounts are as follows: 0.1 mol of 3-aminopropyltriethoxysilane, 0.21 mol of 4-chlorobutanol, 15 mL of triethylamine, and 200 mL of anhydrous tetrahydrofuran. After the reaction is completed, the mixture is cooled to room temperature, the precipitated triethylamine salt is removed by filtration, and the tetrahydrofuran is recovered by rotary evaporation to obtain the intermediate.
[0019] Step A2: Dry nitrogen gas is introduced into the reaction system, the intermediate and anhydrous dichloromethane are added and stirred until homogeneous, the temperature is lowered to 5°C using an ice-water bath, and methacryloyl chloride is slowly added and stirred for 1 hour. The raw material amounts are: 0.1 mol intermediate, 0.2 mol methacryloyl chloride, and 120 mL anhydrous dichloromethane. After the reaction is completed, dichloromethane is recovered by rotary evaporation to obtain the modified monomer.
[0020] Step A3: Take hydrophilic acrylic monomers (acrylic acid and hydroxyethyl acrylate), modified monomers, fluorinated acrylate monomers (perfluoroalkyl ethyl acrylate), and emulsifier (MS-1) and mix them. Then add deionized water and shear emulsify at 1200 rpm for 10 min. Transfer to a reactor and purge with nitrogen. Heat to 75°C and slowly add ammonium persulfate solution (saturated aqueous solution). Stir and react for 4 h. The raw material amounts are: 0.1 mol acrylic acid, 0.1 mol hydroxyethyl acrylate, 34 mmol modified monomer, 20 mmol perfluoroalkyl ethyl acrylate, 0.4 g ammonium persulfate, 1.5 g MS-1 emulsifier, and 400 mL deionized water. After cooling, adjust the pH to 8 with ammonia water to obtain the modified acrylic emulsion.
[0021] II. Formulation of Conductive Coating The raw materials are prepared according to the following weight percentages: conductive agent (a mixture of conductive carbon black and carbon nanotubes in a weight ratio of 1:0.12) 10wt%, wetting agent (Hydropalat WE 3323) 0.2wt%, defoamer (BYK-044) 0.12wt%, thickener (WT-113) 0.3wt%, modified acrylic emulsion 75wt%, and deionized water to make up to 100wt%. Wetting agent, defoamer and deionized water were stirred and premixed. Conductive agent was added and sheared and dispersed at 1800 rpm for 5 min. Then modified acrylic emulsion was added, mixed and defoamed. Finally, thickener was added and mixed evenly to obtain conductive coating with a solid content of 17.5%.
[0022] Example 2: Preparation of conductive coating for lithium batteries. The specific implementation process is as follows: I. Preparation of Modified Acrylic Emulsion Step A1: Dry nitrogen gas is introduced into the reaction system, and 3-aminopropyltriethoxysilane, 4-chlorobutanol and anhydrous tetrahydrofuran are added and stirred until homogeneous. The mixture is heated to 45°C in a water bath, and triethylamine is slowly added and stirred for 7 hours. The raw material amounts are as follows: 0.1 mol of 3-aminopropyltriethoxysilane, 0.21 mol of 4-chlorobutanol, 17 mL of triethylamine, and 200 mL of anhydrous tetrahydrofuran. After the reaction is completed, the mixture is cooled to room temperature, the precipitated triethylamine salt is removed by filtration, and the tetrahydrofuran is recovered by rotary evaporation to obtain the intermediate.
[0023] Step A2: Dry nitrogen gas is introduced into the reaction system, the intermediate and anhydrous dichloromethane are added and stirred until homogeneous, the temperature is lowered to 5°C using an ice-water bath, and methacryloyl chloride is slowly added and stirred for 1 hour. The raw material amounts are: 0.1 mol intermediate, 0.2 mol methacryloyl chloride, and 150 mL anhydrous dichloromethane. After the reaction is complete, dichloromethane is recovered by rotary evaporation to obtain the modified monomer.
[0024] Step A3: Take hydrophilic acrylic monomers (acrylic acid and hydroxyethyl acrylate), modified monomers, fluorinated acrylate monomers (perfluoroalkyl ethyl acrylate), and emulsifier (MS-1) and mix them. Then add deionized water and shear emulsify at 1200 rpm for 10 min. Transfer to a reactor and purge with nitrogen. Heat to 80°C and slowly add ammonium persulfate solution (saturated aqueous solution). Stir and react for 4 h. The raw material amounts are: 0.1 mol acrylic acid, 0.1 mol hydroxyethyl acrylate, 40 mmol modified monomer, 26 mmol perfluoroalkyl ethyl acrylate, 0.35 g ammonium persulfate, 1.8 g MS-1 emulsifier, and 450 mL deionized water. After cooling, adjust the pH to 8 with ammonia water to obtain the modified acrylic emulsion.
[0025] II. Formulation of Conductive Coating The raw materials are prepared according to the following weight percentages: conductive agent (a mixture of conductive carbon black and carbon nanotubes in a weight ratio of 1:0.15) 12wt%, wetting agent (Hydropalat WE 3323) 0.2wt%, defoamer (BYK-044) 0.1wt%, thickener (WT-113) 0.4wt%, modified acrylic emulsion 70wt%, and deionized water to make up to 100wt%. Wetting agent, defoamer and deionized water were stirred and premixed. Conductive agent was added and sheared and dispersed at 1800 rpm for 5 min. Modified acrylic emulsion was then added, mixed and defoamed. Finally, thickener was added and mixed evenly to obtain conductive coating with a solid content of 18.8%.
[0026] Example 3: Preparation of conductive coating for lithium batteries. The specific implementation process is as follows: I. Preparation of Modified Acrylic Emulsion Step A1: Dry nitrogen gas is introduced into the reaction system, and 3-aminopropyltriethoxysilane, 8-chlorooctanol and anhydrous tetrahydrofuran are added and stirred until homogeneous. The mixture is heated to 55°C in a water bath, and triethylamine is slowly added and stirred for 5 hours. The raw material amounts are as follows: 0.1 mol of 3-aminopropyltriethoxysilane, 0.22 mol of 8-chlorooctanol, 20 mL of triethylamine, and 250 mL of anhydrous tetrahydrofuran. After the reaction is completed, the mixture is cooled to room temperature, the precipitated triethylamine salt is removed by filtration, and the tetrahydrofuran is recovered by rotary evaporation to obtain the intermediate.
[0027] Step A2: Dry nitrogen gas is introduced into the reaction system, the intermediate and anhydrous dichloromethane are added and stirred until homogeneous, the temperature is lowered to 5°C using an ice-water bath, and methacryloyl chloride is slowly added and stirred for 1.5 h. The raw material amounts are: 0.1 mol intermediate, 0.2 mol methacryloyl chloride, and 180 mL anhydrous dichloromethane. After the reaction is completed, dichloromethane is recovered by rotary evaporation to obtain the modified monomer.
[0028] Step A3: Take hydrophilic acrylic monomers (acrylic acid and hydroxyethyl acrylate), modified monomers, fluorinated acrylate monomers (perfluoroalkyl ethyl acrylate), and emulsifier (MS-1) and mix them. Then add deionized water and shear emulsify at 1200 rpm for 10 min. Transfer to a reactor and purge with nitrogen. Heat to 90°C and slowly add ammonium persulfate solution (saturated aqueous solution). Stir and react for 3 h. The raw material amounts are: 0.1 mol acrylic acid, 0.1 mol hydroxyethyl acrylate, 44 mmol modified monomer, 26 mmol perfluoroalkyl ethyl acrylate, 0.3 g ammonium persulfate, 2 g MS-1 emulsifier, and 450 mL deionized water. After cooling, adjust the pH to 8 with ammonia water to obtain the modified acrylic emulsion.
[0029] II. Formulation of Conductive Coating The raw materials are prepared according to the following weight percentages: conductive agent (a mixture of conductive carbon black and carbon nanotubes in a weight ratio of 1:0.18) 15wt%, wetting agent (Hydropalat WE 3323) 0.3wt%, defoamer (BYK-044) 0.15wt%, thickener (WT-113) 0.4wt%, modified acrylic emulsion 60wt%, and deionized water to make up to 100wt%. Wetting agent, defoamer and deionized water were stirred and premixed. Conductive agent was added and sheared and dispersed at 1800 rpm for 5 min. Then modified acrylic emulsion was added, mixed and defoamed. Finally, thickener was added and mixed evenly to obtain conductive coating with a solid content of 22.1%.
[0030] Example 4: Preparation of conductive coating for lithium batteries. The specific implementation process is as follows: I. Preparation of Modified Acrylic Emulsion Step A1: Dry nitrogen gas is introduced into the reaction system, and 3-aminopropyltriethoxysilane, 8-chlorobutanol and anhydrous tetrahydrofuran are added and stirred until homogeneous. The mixture is heated to 50°C in a water bath, and triethylamine is slowly added and stirred for 6 hours. The raw material amounts are as follows: 0.1 mol of 3-aminopropyltriethoxysilane, 0.22 mol of 8-chlorobutanol, 20 mL of triethylamine, and 250 mL of anhydrous tetrahydrofuran. After the reaction is completed, the mixture is cooled to room temperature, the precipitated triethylamine salt is removed by filtration, and the tetrahydrofuran is recovered by rotary evaporation to obtain the intermediate.
[0031] Step A2: Dry nitrogen gas is introduced into the reaction system, the intermediate and anhydrous dichloromethane are added and stirred until homogeneous, the temperature is lowered to 5°C using an ice-water bath, and methacryloyl chloride is slowly added and stirred for 1.5 h. The raw material amounts are: 0.1 mol intermediate, 0.2 mol methacryloyl chloride, and 160 mL anhydrous dichloromethane. After the reaction is completed, dichloromethane is recovered by rotary evaporation to obtain the modified monomer.
[0032] Step A3: Take hydrophilic acrylic monomers (acrylic acid and hydroxyethyl acrylate), modified monomers, fluorinated acrylate monomers (perfluoroalkyl ethyl acrylate), and emulsifier (MS-1) and mix them. Then add deionized water and shear emulsify at 1200 rpm for 10 min. Transfer to a reactor and purge with nitrogen. Heat to 85°C and slowly add ammonium persulfate solution (saturated aqueous solution). Stir and react for 4 h. The raw material amounts are: 0.1 mol acrylic acid, 0.1 mol hydroxyethyl acrylate, 38 mmol modified monomer, 22 mmol perfluoroalkyl ethyl acrylate, 0.4 g ammonium persulfate, 2 g MS-1 emulsifier, and 500 mL deionized water. After cooling, adjust the pH to 8 with ammonia water to obtain the modified acrylic emulsion.
[0033] II. Formulation of Conductive Coating The raw materials are prepared according to the following weight percentages: conductive agent (a mixture of conductive carbon black and carbon nanotubes in a weight ratio of 1:0.15) 13wt%, wetting agent (Hydropalat WE 3323) 0.3wt%, defoamer (BYK-044) 0.12wt%, thickener (WT-113) 0.3wt%, modified acrylic emulsion 65wt%, and deionized water to make up to 100wt%. Wetting agent, defoamer and deionized water were stirred and premixed. Conductive agent was added and sheared and dispersed at 1800 rpm for 5 min. Modified acrylic emulsion was then added, mixed and defoamed. Finally, thickener was added and mixed evenly to obtain conductive coating with a solid content of 19.7%.
[0034] For the comparative example, commercially available Incellion™ Pr 1011 was used, and the modified acrylic emulsion from Example 4 was adjusted to the same solids content, with the rest of the process being exactly the same.
[0035] The conductive coating prepared above was applied to the surface of aluminum foil and dried at 80℃ for 24 hours to prepare a sample with a coating thickness of 15±1μm. Coating sheet resistance test: The surface sheet resistance of the dried coating is measured using a four-probe sheet resistance tester. Coating adhesion test: The adhesion of the coating was tested using the cross-cut test method according to GB / T 9286-2021 standard. Electrolyte swelling resistance test: The coated sample was immersed in an electrolyte solution (1M LiPF6 in EC / DMC=1:1 v / v) at 60℃ for 72 hours. After removal, it was quickly wiped dry, and its weight change rate was measured. The sheet resistance was then tested again, and the sheet resistance change rate was calculated. Simulated Cyclic Stability Test: To accurately evaluate the intrinsic structural stability and interfacial resistance retention of the conductive coating described in this invention under long-term electrochemical cycling conditions, a simulated battery cycling test method was adopted. An aluminum foil coated with the coating to be tested was used as the working electrode, and a lithium metal sheet was used as the counter electrode and reference electrode. The electrolyte was the same as above, and a coin cell simulated battery was assembled. At a 1C charge-discharge rate, 500 cycles were performed. After every 100 cycles, the electrode was removed, cleaned and dried, and the sheet resistance of the coating was tested and the rate of change was calculated.
[0036] The specific test results are shown in Table 1 below:
[0037] As can be seen from the test results in Table 1, the conductive coating prepared in the example has a significantly lower initial sheet resistance than the comparative example after curing, and exhibits strong adhesion, good anti-swelling properties, and extremely low sheet resistance change rate after long-term cycling, demonstrating excellent stability.
[0038] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0039] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A conductive coating for lithium batteries, characterized in that, The specific components are: 10-15 wt% conductive agent, 0.2-0.3 wt% wetting agent, 0.1-0.15 wt% defoamer, and 0.3-0.4 wt% thickener, with the balance being modified acrylic emulsion and deionized water; The modified acrylic emulsion is prepared by the following method: Step A1: Under dry nitrogen protection, 3-aminopropyltriethoxysilane, chloromonool and anhydrous tetrahydrofuran are mixed and stirred at 40-55℃ for 5-8 hours to obtain the intermediate. Step A2: Under dry nitrogen protection, the intermediate and anhydrous dichloromethane are mixed, cooled in an ice-water bath, and then methacryloyl chloride is slowly added and stirred for 1-1.5 h. After that, the reaction is continued at room temperature for 2-3 h. The modified monomer is obtained after treatment. Step A3: Mix the hydrophilic acrylic monomer, modified monomer, fluorinated acrylate monomer and emulsifier, then add deionized water for shear emulsification. Under nitrogen protection, heat to 75-90℃, slowly add ammonium persulfate solution and stir for 3-4 hours. After cooling, adjust the pH to 8 with ammonia water to obtain the modified acrylic emulsion.
2. The conductive coating for lithium batteries according to claim 1, characterized in that, Chlorinated monools are one of 4-chlorobutanol and 8-chlorooctanol.
3. The conductive coating for lithium batteries according to claim 2, characterized in that, The molar ratio of 3-aminopropyltriethoxysilane to chloromonool is 1:2.1-2.
2.
4. The conductive coating for lithium batteries according to claim 3, characterized in that, The molar ratio of the intermediate to methacryloyl chloride is 1:
2.
5. The conductive coating for lithium batteries according to claim 4, characterized in that, The molar ratio of hydrophilic acrylic monomer, modified monomer and fluorinated acrylate monomer is 1:0.17-0.22:0.1-0.
13.
6. The manufacturing process of a conductive coating for lithium batteries according to any one of claims 1-5, characterized in that, Specifically, the wetting agent, defoamer, and deionized water are premixed, a conductive agent is added and sheared and dispersed, then a modified acrylic emulsion is added, mixed and defoamed, and finally a thickener is added and mixed evenly to obtain a conductive coating.
7. The production process of a conductive coating for lithium batteries according to claim 6, characterized in that, The conductive agent is a mixture of conductive carbon black and carbon nanotubes in a weight ratio of 1:0.12-0.
18.
8. The production process of a conductive coating for lithium batteries according to claim 6, characterized in that, The solid content of conductive coatings is 17-23%.
